Predicting the Performance of Initial Public Offerings: Should Human Resource Management be in the Equation? - Welbourne, Theresa M.; Andrews, Alice O. (Academy of Management Journal, 1996)
Population ecology is used to explain the role of human resource management (HRM) in enhancing the performance of initial public offering (IPO) companies. We examined the determinants of structural inertia and developed hypotheses on the relationship between HRM and organizational performance. The results indicate that two human resource variables, human resource value and organization-based rewards, predict initial investor reaction and long-term survival. The rewards variable negatively affects initial performance but positively affects survival.